Instructional Technology in the 21\(^st\) Century: Tools and Strategies for Effective Teaching and Learning - Dr. Jacob Manu; Dr. Samuel Antwi (Instructional Technology in the 21\(^st\) Century: Tools and Strategies for Effective Teaching and Learning, Edition 1, 2025)
Instructional Technology in the 21st Century: Tools and Strategies for Effective Teaching and Learning is a user-friendly book. It is churned from research, best practices as well as authors’ extensive knowledge of classroom dynamics. The book is written to help university students, educators, student-teachers as well as in-service teachers to overcome their technology integration fears in the classroom. The intention of the authors is to bring to the fore the numerous learning opportunities that have become available as a result of 21st-century technologies. Instructional Technology in the 21st Century: Tools and Strategies for Effective Teaching and Learning discusses the historical antecedents of the Instructional Design field, technology use in Ghana, digital tools and software applications by Morrison and Lowther (2010), challenges of technology use in Ghana, Instructional Design models (Nine Conditions of Learning, ASSURE, NTEQ and ADDIE), data collection techniques, e-learning as well as modern applications that educators, teachers, and students can use to facilitate learning and improve performance. There are three main features of the book that are unique from most of the books on technology. First, the authors attempt to explain the problem that each of the chapters seeks to address. This is meant to help readers become aware of some of the burning issues as well as have something to think about as they read along. Second, the authors have strategically placed reflections in the various sections. These reflections are to help the readers think and ask the right questions and possibly generate creative and critical answers for some of the challenges we face. Third, there are brief suggestions on how to integrate simple tools into the teaching and learning process. Depending on the context within which the book is to be used, teachers are welcome to add or take away aspects that might not work within their environments. From the standpoint of instructional design and technology, we need to be concerned with the main principles that underlie technology use.